Soilgrid Component with Permafrost Use Case ... - Overeem, Irina; Gan, Tian (NSF Arctic Data Center, 2025)
Permafrost dynamics are highly dependent on soil properties, like soil texture, soil moisture and soil depth. Modelers need to time and time again parametrize their study sites with this type of data. To facilitate this process, we designed "data components". Data Components, which are software packages that provide access to particular research datasets or types of data. Because they use a standard interface based on the Basic Model Interface (BMI), Data Components can function as plug-and-play components within modeling frameworks to facilitate seamless data–model integration. Specifically the Soilgriids data component was designed to allow permafrost modelers to auto-mine soil data and connect it to permafrost models. This is python code to retrieve SoilGrid global soil data to work with a permafrost model. An example use case is described in: Gan,T., Tucker,G., Hutton, E., Piper, M., Overeem, I., Kettner, A., Campforts, B., Moriarty, J., Undzis, B., Pierce, E., McCready, L., 2024. CSDMS Data Components: ...